2018
DOI: 10.1002/2017jd027171
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Central Indian Ocean Mode in CESM: Implications for the Indian Summer Monsoon System

Abstract: The simulation of the Indian summer monsoon and its pronounced intraseasonal component in a modern climate model remains a significant challenge. Recently, using observations and reanalysis products, the central Indian Ocean (CIO) mode was found to be a natural mode in the ocean‐atmosphere coupled system and also shown to have a close mechanistic connection with the monsoon intraseasonal oscillation (MISO). In this study, the simulation of the actual CIO mode in historical Community Earth System Model (CESM) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…Thus, the necessary condition for barotropic instability cannot be satisfied. Such results are consistent with Zhou et al (2018), which concluded that the bias in simulating the meridional structures of trueu¯y was a critical reason for the misrepresentation of the CIO mode in CESM.…”
Section: Dynamics Behind Different Cio Mode Simulationssupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, the necessary condition for barotropic instability cannot be satisfied. Such results are consistent with Zhou et al (2018), which concluded that the bias in simulating the meridional structures of trueu¯y was a critical reason for the misrepresentation of the CIO mode in CESM.…”
Section: Dynamics Behind Different Cio Mode Simulationssupporting
confidence: 92%
“…The CIO mode is not sensitive to the domain of EOF analysis or to the data that are used to extract this mode. Previous studies have shown that the CIO mode (represented with the CIO mode index) has a high simultaneous correlation with MISO (Zhou et al, 2017a(Zhou et al, , 2018 but it does not have a significant linear dependence on ENSO or IOZDM (Zhou et al, 2017b). Therefore, it is expected that the CIO mode should contribute to improve the prediction of MISO as an independent predictand.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations